Effect of Vitamin A Supplementation on Acute Respiratory Infections among Children Under Five in Konawe District - Lisnawati Lisnawati (Poltekkes Kemenkes Palu, 2025)
Acute Respiratory Infections (ARIs) remain one of the leading causes of morbidity and mortality among children under five in Indonesia, particularly in rural areas where access to health services may be limited. Vitamin A plays a key role in supporting immune function and maintaining epithelial integrity, which can influence the risk and severity of ARI. This study examined the relationship between vitamin A supplementation and ARI severity among children under five in the service area of Morosi Community Health Center, Konawe District. An analytical cross-sectional study was conducted using secondary data from 67 children diagnosed with ARIs in 2022. Vitamin A supplementation data were categorized as low (≤1 dose/year) or adequate (≥2 doses/year), while ARI severity was classified as mild, moderate, or severe based on clinical records. The analysis showed that more than half of the children (55.2%) received low vitamin A supplementation. A significant association was found between vitamin A supplementation and ARI severity (p = 0.007), with mild ARI predominating among children with low supplementation and moderate cases being more common among those with adequate supplementation. These findings highlight the important role of vitamin A supplementation in child health programs. Strengthening routine supplementation, particularly in underserved communities, may help reduce ARI-related morbidity. Further longitudinal or interventional studies are needed to confirm these associations.